Analisa Keandalan Struktur pada Container Crane SWL 40 Ton Menggunakan Metode Monte Carlo - Cahyo Dwi Satria; Adi Wirawan Husodo; Mohamad Hakam (Proceedings Conference On Design Manufacture Engineering And Its Application, 2020)
In its operation, container crane are significantly affected by usage and environmental conditions. The structure of the container crane must be able and show the best performance in overcoming the loading and environmental conditions. This study aims to determine the reliability of the container crane structure of the container crane type quay crane with SWL 40 tons. The method used is perform a static analysis by calculating the value of von mises stress and deflection due to loading condition. The loads use variation, 60% SWL, 100% SWL, and 110% SWL. To calculate the reliability of the structure, the author uses the Monte Carlo method. With the help of CATIA V5R21 software to model and perform FEM analysis of container crane structures and the result compared with manual calculation. The error rate between software and normal calculation is 6,86 %. The critical point of stress occurs at boom. The results of the analysis of the reliability of the container crane structure using Monte Carlo show that the reliability value of the structure after 21 years is decreasing.